Health workforce data needed to minimize inequities associated with health worker migration/Importance des donnees sur les professionnels de la sante pour reduire les inegalites associees a leur migration/Se necesitan datos sobre el personal sanitario para minimizar las desigualdades asociadas a la migracion de los profesionales sanitarios - Walton-Roberts, Margaret; Bourgeault, Ivy L (Bulletin of the World Health Organization, 2024)
A persistent challenge with health-worker migration is the inequities it creates. To minimize these inequities, systems of global governance of health-worker migration have arisen which include various global codes of practice, agreements and reporting requirements. Reporting that is rigorous, open and transparent, and subject to scrutiny from the public, researchers, civil society organizations and other interested stakeholders, is important. One element of these codes and agreements with perhaps the greatest potential to deal with the impact of health-worker migration is more robust planning of the health workforce to address the goal of self- sufficiency. Open platforms for data sharing enable engagement of the public and stakeholders with data on the distribution and national origin of health workers and reveal policy strengths and weaknesses related to health-workforce planning. We explore recent policies directed at reducing the inequities from health-worker migration. While many of the examples used focus on nurses and doctors, the issues discussed are relevant to all cadres of internationally trained health workers.